Fevered Inheritances: Ethics of Care and Donor Power in Starchives - Armendariz, Anastasia; Orazem, Kate (Archivaria, 2025)
In the three decades since its English publication, Jacques Derrida’s Archive Fever: A Freudian Impression has enjoyed an enthusiastic reception among theorists of the archive across disciplines, generating a remarkable variety of responses, applications, and critiques. However, as the records of critical theorists enter our archives, this discourse has paid scant attention to the legal conflict following the acquisition of Derrida’s papers as the flagship collection of the Critical Theory Archive at the University of California, Irvine (“the UCI affair”). This article seeks to explore and amend the meaning of that gap as itself an archival silencing.Analyzing the UCI affair as an element of the provenance of the Derrida Papers, we position that collection, and the conflicts surrounding it, as a valuable case study regarding the translation into praxis of feminist archival theories positing a radical ethics of care as a key professional commitment. Applying these theories to this case, we examine the increasingly uneasy relationships between the university, its donors, its archival agents, and the state, and the circuits of capital that constitute and animate those entanglements. We argue that this clarifies how archival collections, as contractually mediated by universities, can preserve creators’ perspectives and their social, professional, and discursive power over time. We examine the implications of this function through the lens of feminist and queer theories of the archive and engage with theorizations of the neoliberal public university in the United States to analyze the intersecting axes of power at play in the UCI affair and among various archival stakeholders. Considering Derrida’s limited-access papers as a paradigm of the flagship collection or starchive opens up broader questions about the competing priorities of donors, institutional administrators, researchers, and archival practitioners. Finally, returning to feminist theories of affect in the archives, we consider how frameworks like radical empathy and restorative justice ask us to ground both theoretical work and archival practice in an ethics of care that embraces the inevitability of harm and the paradoxical necessity and impossibility of repair, leading us to a critical stance of radical humility in service of material solidarity with all archival labourers.